INDIKATOR KINERJA TELEKOMUNIKASI DALAM PEMANFAATAN MENARA SELULER BERSAMA - Paronda, Abdul Hafid (JREC (Journal of Electrical and Electronics), 2012)
Abstract Enhancement of mobile cellular subscribers number need amount of cell site within it BTS supporting system. It face on government policy that arrange the utilizing of the cellular common tower in order to maintain the esthetical planology city management. Telecommunication performance system tend to change down as impact of telecommunication operator co-existence on cellular common tower and subscribers intensity around the cell site.Keywords : Telecommunication performance, common cellular tower, esthetical city management.